Pengaruh Hardskill Dan Softskill Terhadap Kinerja Karyawan Pada Masa Pandemi Covid-19 (Studi Pada PT.Solindo Tama Jaya) - Erika Febriari Saputri; Moeheriono; Winarto (Aplikasi Administrasi: Media Analisa Masalah Administrasi, 2022)
Various countries are experiencing many changes in the economic field that caused by Covid-19, which has made the economy unstable, including Indonesia. Companies experience the impact of this pandemic that continues to do business despite of the downturn. For the cost of human resources, companies must choose those who have good performance and skills that are in accordance with the company. This study aims to determine the effect of hard skills on the performance of employees of PT. Solindo Tama Jaya, the effect of soft skills on the performance of employees of PT. Solindo Tama Jaya, the effect of hard skills and soft skills on the performance of employees of PT. Solindo Tama Jaya. This study uses a quantitative method with an associative approach. This type of research uses explanatory research. The sample in this study amounted to 93 employees using simple random sampling. This research is categorized in a research questionnaire with research instruments in the form of using validity tests, reliability tests, classical assumption tests, multiple linear regressions, t tests, F tests, coefficient correlation (R) and coefficient determination (R2). The results of multiple linear regression tests that the t test partially hard skills have a significant positive effect on employee performance evidenced by t count 6.640 with a significance value of 0.000, soft skills have a significant positive effect on employee performance as evidenced by t count 2.716 with a significance value of 0.008, and the F test is evidenced by the results of hard skills and soft skills having a positive effect on employee performance with an F value of 29.394 with a significance of 0.000. Value coefficient correlation (R) 0.629 or 62,9% and coefficient determination (R2) 0.382 or 38,2%.